Psychiatric and substance use disorders in HIV/hepatitis C virus (HCV)‐coinfected patients: does HCV clearance matter? [Agence Nationale de Recherche sur le SIDA et les Hépatites Virales (ANRS) HEPAVIH CO13 cohort]. Issue 10 (November 2016) - Michel, L; Lions, C; Winnock, M; Lang, J‐P; Loko, M‐A; Rosenthal, E; Marchou, B; Valantin, M‐A; Morlat, P; Roux, P; Sogni, P; Spire, B; et al.
Abstract : Objectives: The objective of this nested study was to assess the prevalence of psychiatric disorders in a sample of HIV/hepatitis C virus (HCV)‐coinfected patients according to their HCV status. Methods: The nested cross‐sectional study, untitled HEPAVIH‐Psy survey, was performed in a subset of HIV/HCV‐coinfected patients enrolled in the French Agence Nationale de Recherche sur le SIDA et les Hépatites Virales (ANRS) CO13 HEPAVIH cohort. Psychiatric disorders were screened for using the Mini International Neuropsychiatric Interview (MINI 5.0.0). Results: Among the 286 patients enrolled in the study, 68 (24%) had never received HCV treatment, 87 (30%) were treatment nonresponders, 44 (15%) were currently being treated and 87 (30%) had a sustained virological response (SVR). Of the 286 patients enrolled, 121 patients (42%) screened positive for a psychiatric disorder other than suicidality and alcohol/drug abuse/dependence, 40 (14%) screened positive for alcohol abuse/dependence, 50 (18%) screened positive for drug abuse/dependence, 50 (17.5%) were receiving an antidepressant treatment and 69 (24%) were receiving an anxiolytic. Patients with an SVR did not significantly differ from the other groups in terms of psychiatric disorders. Patients receiving HCV treatment screened positive less often for an anxiety disorder. The highest rate of drug dependence/abuse was among HCV treatment‐naïve patients. Conclusions: Psychiatric disorders were frequent in HIV/HCV‐coinfected patients and their rates were comparable between groups, even for patients achieving an SVR. Our results emphasize the need for continuous assessment and care of coinfected patients, even after HCV clearance. Drug addiction remains an obstacle to access to HCV treatment. Despite the recent advent and continued development of directly acting antiviral agents (DAAs), it is still crucial to offer screening and comprehensive care for psychiatric and addictive disorders.